Artes Apodemicae and Early Modern Travel Culture, 1550-1700 - Enenkel, Karl A.E., author.
1 online resource.
Keywords: This volume explores the early modern manuals on travelling ( Artes apodemicae ), a new genre of advice literature that originated in the sixteenth century, when it became communis opinio among intellectuals that travelling was an important means of acquiring knowledge and experience, and that an extended tour abroad was a vital, if not indispensable part of humanist, academic and political education. In this volume, the formation of this new genre, between 1550 and 1700, is studied in its historical, social and cultural context. Furthermore, the volume examines the impact of this new genre on the acquisition and collection of knowledge in the early modern period, empirical or otherwise. Contributors: Justin Stagl, Karl Enenkel, Jan Papy, Thomas Haye, Robert Seidel, Gabor Gelléri, Bernd Roling, Harald Hendrix, Jan L. de Jong, Kerstin Maria Pahl, Johanna Luggin, Marc Laureys, and Justina Spencer.